An Overview of Linguistics and Education: A Bibliometric Analysis - Am, St. Asriati; Nurlaili, Nurlaili; Ridwan, Ridwan; Safira, Ega; AM, St Asmayanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study attempts to identify the main linguistic education topic that is an overview on linguistics and education: A bibliometric analysis from 2015 to 2023. It employed a quantitative method with a bibliometric literature review. The 309 documents (48 papers, 218 articles, and 43 scientific papers) maintained in the Mendeley applications formed the source of the research data. This study took the data from Google Scholar to obtain some researches related to the topic by using Public or Perish application. VOS viewer software was applied for the bibliometric analysis of the data. Numerous publications, citation analysis, and the visualization of term co-occurrence patterns are all part of this research. The results of data analysis indicate that the three different kinds of documents considered in this study are distributed as follows:  articles (n = 262) made up 85% of the total number of documents, followed by proceeding papers (n = 5) with 2% and books (n = 42) with 13%. A total of 716 keywords, beginning with 309, were discovered. The analysis of the different clusters revealed development of a methodology known as systemic functional linguistics.